Indonesian Islamic Movement in the Early 20th Century - Helmi Muslimah; Inda Upi Nursania Kulsum; Siti Yani Yuliani; Lina Pusvisasari (al-Wadhih: Journal of Islamic History and Civilization, 2025)
The struggle for Indonesian independence is closely related to the role of Muslims, both before, during, and after independence in maintaining the nation's sovereignty. This is reflected in the various efforts made by Muslims through political approaches, the formation of organizations, and acts of resistance against colonialism. The birth of these movements was influenced by various factors that developed at that time, which then gave rise to the dynamics of movements among Muslims, especially in the 20th century.